The efforts of the scholars of the city of Urmia in scientific life during the centuries (7th-9th AH / 13th-15th AD) - قادر, كامل اسود; خضر, مهدى قادر (Sulaimani Journal for Humanities, 2019)
This research is about the attempt of Urmia scientist in` (7 A D centuries / 13-15 for higre ) in this century a number of prominent scientist in different field has appeared. They try their best to service the Islamic civilization Islamic countries has always have scientists of different types such as the science of readings (Al Qrat ), the saying of the profit ( AL hadeeth), worshiping science and logical science. In addition of having religious ranks such as noblemen syndicate which is supervising profit successor . It is worth mentioning that Urmia scientists has appeared in the cities of Egypt and Bilad Al sham, they contribute to the development of Islamic civilization, moreover, they teach at academic setting in Egypt and Bilad Al sham. All these is clearly mentioned in the modern history.